The effects of AER and eGFR on outcomes of CVD in patients with T2DM in an urban community over 8 years of multifactorial treatment: the Beijing Communities Diabetes Study 18 - Zhang XL; Yuan MX; Wan G; Yang GR; Li D; Fu HJ; Zhu LX; Xie RR; Zhang JD; Lv YJ; Li YL; Du XP; et al. (Dove Medical Press, 2018)
Xue-Lian Zhang,1 Ming-Xia Yuan,1 Gang Wan,2 Guang-Ran Yang,1 Dong-Mei Li,3 Han-Jing Fu,1 Liang-Xiang Zhu,1 Rong-Rong Xie,1 Jian-Dong Zhang,4 Yu-Jie Lv,5 Yu-Ling Li,6 Xue-Ping Du,7 Zi-Ming Wang,8 Xue-Li Cui,9 De-Yuan Liu,10 Ying Gao,11 Shu-Yan Cheng,12 Qian Wang,13 Yu Ji,14 Guang-Wei Li,15,16 Shen-Yuan Yuan1 1Department of Endocrinology, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Medical Records and Statistics Department, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Clinical and Translational Science Institute, School of Medicine and Dentistry, University of Rochester, Rochester, NY, USA; 4Department of General Practice, Jinsong Community Health Service Center, Beijing, People’s Republic of China; 5Department of General Practice, Cuigezhuang Community Health Service Center, Beijing, People’s Republic of China; 6Department of General Practice, Xinjiekou Community Health Service Center, Beijing, People’s Republic of China; 7Department of General Practice, Yuetan Community Health Service Center of Fuxing Hospital, Capital Medical University, Beijing, People’s Republic of China; 8Department of General Practice, Jiangtai Community Health Service Center, Beijing, People’s Republic of China; 9Department of General Practice, Sanlitun Community Health Service Center, Beijing, People’s Republic of China; 10Department of General Practice, Zuojiazhuang Community Health Service Center, Beijing, People’s Republic of China; 11Department of General Practice, The First People’s Hospital of Chongwen District, Beijing, People’s Republic of China; 12Department of General Practice, Balizhuang Community Health Service Center, Beijing, People’s Republic of China; 13Department of General Practice, Majiapu Community Health Service Center, Beijing, People’s Republic of China; 14Department of Endocrinology, Beijing Aerospace General Hospital, Beijing, People’s Republic of China; 15Department of Endocrinology, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 16Center of Endocrinology and Cardiovascular Disease, Department of Endocrinology, National Center of Cardiology and Fuwai Hospital, Beijing, People’s Republic of China Objective: It is well known that diabetic kidney disease is a risk factor for cardiovascular diseases (CVD) in patients with type 2 diabetes mellitus (T2DM). In this study, the effects of urine albumin excretion rate (AER) and estimated glomerular filtration rate (eGFR) on CVD outcomes were analyzed in a population of T2DM. Methods: The study was carried out using recorded information of a cohort study. A total of 1,914 patients with T2DM with no prevalent CVD were enrolled in an 8 years prospective study and received multifactorial intervention. The risk of CVD outcomes was assessed according to chronic kidney disease staging, which was categorized using AER (mg/d) and eGFR (mL/min/1.73 m2). The effects of AER and eGFR on risk of CVD onset were also analyzed. Results: During the follow-up period (median 6.8 years), 71 CVD events occurred. At baseline, those with AER ≥300 mg/d and coexisting eGFR 60–89 mL/min/ 1.73 m2 or <60 mL/min/1.73 m2 showed increased risk for CVD outcomes when compared with “no chronic kidney disease” (AER <30 mg/d and eGFR ≥90 mL/min/1.73 m2). The increased CVD risk was observed in patients who progressed to AER ≥30 mg/d during the follow-up period, whereas patients who progressed to eGFR <90 mL/min/1.73 m2 alone showed no increased CVD risk. During the follow-up period, after multifactorial intervention, 8.7% patients with microalbuminuria and 1.8% patients with overt nephropathy reversed to normoalbuminuria or microalbuminuria. Conclusion: AER is a more sensitive predictor than eGFR for CVD outcomes in T2DM patients. Overt nephropathy can be reversed after multifactorial intervention. Keywords: albumin excretion rate, cardiovascular disease, chronic kidney disease, diabetic nephropathy, glomerular filtration rate